Acupuncture effects on pain and health status in women with fibromyalgia: a randomized clinical trial - Baelz, Gustavo Urbanetto; Silva, Antonio Marcos Vargas da; Duarte, Bárbara Santos Luccas; Steffen, Elizandra Leal; Silva, José Edson Paz da; Signori, Luis Ulisses (Acta Scientiarum. Health Sciences, 2023)
This study aims to evaluate the effects of acupuncture on pain and health status in women with fibromyalgia. The present randomized, controlled, double-blind clinical trialwas carried out with one sample of 40 women diagnosed with fibromyalgia .They were randomized into one acupuncture group (n = 20; 51.7 ± 6.5 years old) and one sham acupuncture group (n = 20; 49.7 ± 7.2 years old). Acupuncture (points: pericardium 6, heart 7, large intestine 4, stomach 36, spleen-pancreas 6, and liver 2, variable depth with Deqi stimulation) and sham acupuncture (15mm lateral to the acupoint, outside the meridian line) were performed for 30min., once a week, and with a four-week follow-up. Pain (Visual Analogue Scale), algometry (lateral epicondyle, trapezius, suboccipital, 2nd rib), and health status (Fibromyalgia Impact Questionnaire) was assessed before the first and after the last intervention. Data were analyzed by the intention-to-treat.Acupuncture reduced pain by 16% (p<0.001) and improved health status by 21% (p<0.001). The improvement in health status (p<0.001) is due to the increased ability to work and go out, and reduced pain, fatigue, tiredness, and depression. Acupuncture reduced pain and improved health statusin women with fibromyalgia.